2018
DOI: 10.31768/2312-8852.2018.40(3):243-248
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Survival of Patients With Breast Cancer Depending on Age, Molecular Subtype of Tumor and Metabolic Syndrome

Abstract: Aim: To analyze the survival of patients with breast cancer (BC) depending on age, molecular subtype of the tumor and the presence of metabolic syndrome. Patients and Methods: We have analyzed the results of examination and treatment of 202 patients with BC of stages I–III. The patients were distributed by age into 2 groups. The group 1 included 86 elderly patients (from 65 to 84 years old), the group 2 — 116 younger patients (from 32 to 64 years). An overall 1-, 3- and 5-year survival rates of the treated pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 7 publications
0
17
0
2
Order By: Relevance
“…For the remaining 29 potential relevant studies that underwent full text review, 20 were further excluded because eight of them were not cohort studies, two did not include MetS as exposure of interest, eight included patients without breast cancer at baseline, and the other two were repeated abstracts of the included studies. Finally, nine follow-up studies were included [15][16][17][18][19][20][21][22][23]. Li et al Diabetol Metab Syndr (2020) 12:10…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…For the remaining 29 potential relevant studies that underwent full text review, 20 were further excluded because eight of them were not cohort studies, two did not include MetS as exposure of interest, eight included patients without breast cancer at baseline, and the other two were repeated abstracts of the included studies. Finally, nine follow-up studies were included [15][16][17][18][19][20][21][22][23]. Li et al Diabetol Metab Syndr (2020) 12:10…”
Section: Literature Searchmentioning
confidence: 99%
“…Overall, this meta-analysis included nine cohort studies [15][16][17][18][19][20][21][22][23] with 17,892 women with breast cancer. Since three studies provided data based on the status of hormone receptors (HR) of the cancer [16,19,20] and one study based on age stratification [22], these datasets were included separately. The characteristics of the included cohorts were shown in Table 1.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have indicated the close association between MetS and increased risk of recurrence and overall mortality due to BC (7,9,10). Based on the intrinsic molecular subtypes, some researchers reported that a non-significant trend for increased risk of mortality was observed among the hormone-receptor (HR)positive patients with BC and MetS (11,12). Moreover, the lack of data on Her-2 status may affect the conclusion of the impression of Mets on the prognosis of early BC, which is based on the molecular profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the lack of data on Her-2 status may affect the conclusion of the impression of Mets on the prognosis of early BC, which is based on the molecular profiles. Accordingly, several related studies have shown conflicting results because of the hypothesis that the different components of MetS may be involved in the development and prognosis of the molecular subtypes of BC (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%